Strategi Kepala Sekolah Menengah Atas Dalam Memaknai Domain Keterampilan Era Revolusi Industri 4.0 - Lina Lina; Nurul Ulfatin; Sultoni Sultoni (Graduate School of Universitas Negeri Malang, 2022)
The purpose of this article is to identify the strategies of high school principals in interpreting the skill domains that high school students must possess in the Industrial Revolution 4.0 era. This research uses a qualitative approach with a multi-case study design in one of the public and private high schools in Malang. The results show that the principal's strategy depends on the characteristics of the school. In private schools, the strategy begins with building a school management system; analyzing the relevance of the vision; adjust school programs in line with the vision; and increase collaboration with external parties. In public schools, the strategy begins with analyzing the relevance of the vision; changing the mission as the school's operational focus; and adapting school programs.Tujuan dari artikel ini adalah untuk mengidentifikasi strategi kepala sekolah menengah atas dalam memaknai domain keterampilan yang harus dimiliki siswa SMA di era Revolusi Industri 4.0. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi multikasus di salah satu SMA negeri dan swasta di Malang. Hasil penelitian memperlihatkan strategi kepala sekolah bergantung pada karakteristik sekolah. Pada sekolah swasta, strategi diawali dengan membangun sistem pengelolaan sekolah; menganalisis relevansi visi; menyesuaikan program-program sekolah selaras dengan visi; serta meningkatkan kolaborasi dengan pihak eksternal. Pada sekolah negeri, strategi diawali dengan menganalisis relevansi visi; mengubah misi sebagai fokus operasional sekolah; serta menyesuaikan program-program sekolah.